A scheduling algorithm for bandwidth aggregation in heterogeneous wireless network - Masud, M.H.; Abd Latif, Suhaimi; Anwar, Farhat; Alam, M. K. (2014)
Next generation wireless communication systems are being devised with the vision of heterogeneity where multiple wireless technologies are co-existing. Bandwidth is one of wireless resources that can be aggregated among the available technologies in a particular area. Bandwidth aggregation has been considered one of the effective solutions for high bandwidth required applications in Heterogeneous Wireless Network (HWN). However, the selection of Radio Access Technology (RAT) for aggregation in HWN is a great challenge. This paper proposes a scheduling algorithm for RAT selection in HWN for bandwidth aggregation. It is expected that the proposed algorithm can select the minimum set of RAT from the available RATs based on the required application's demand that will improve the throughput and utilizes the wireless resources.